Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (CoRR)

"Make Them Change it Every Week!": A Qualitative Exploration of Online Developer Advice on Usable and Secure Authentication - Klemmer, Jan H.; Gutfleisch, Marco; Stransky, Christian; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (CoRR)

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Die Transformation zum Smart Service-Anbieter - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Rasor, Anja; Ködding, Patrick; Wegel, Arthur; Fischer, Lena

Einstieg in die Kreislaufwirtschaft: Integrative Planung von Produkten und Geschäftsmodellen - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Pierenkemper, Christoph; Hensen, Christian

A Data Map for Product Creation: Tasks, Data Flows, and IT-Systems from the Initial Idea to the Start of Production - Ködding, Patrick; Tissen, Denis; Koldewey, Christian (Proceedings of the 56th CIRP Conference on Manufacturing Systems, CIRP CMS ‘23)

A Framework For The Domain-Driven Utilization Of Manufacturing Sensor Data In Process Mining: An Action Design Approach - Brock, Jonathan; Rempe, Niclas; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (5th Conference on Production Systems and Logistics)

Conceptual Framework for Prescriptive Analytics based on decision Theory - Weller, Julian; Migenda, Nico; Wegel, Arthur; Kohlhase, Martin; Schenk, Wolfram; Dumitrescu, Roman (IEEE ADACIS 2023)

A Reference Process Model for Scenario-based Foresight - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the XXXII ISPIM Innovation Conference)

Enhancing Risk Management for Digitalisation Projects in the Context of Socio-Technical Systems - Menzefricke, Jörn Steffen; Koldewey, Christian; Dumitrescu, Roman (The Digital Twin of Humans)

The Role of Design in interdisciplinary Product Development – Challenges, Research Approaches and Further Research needs - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In global competition, companies are continuously searching for a competitive advantage. A growing number of companies have identified the design of their products as a major success factor. The promises for companies associated with outstanding design are extremely attractive, ranging from better customer experience to higher sales growth. But even though the advantages of design seem to be compelling, companies are still having difficulties in leveraging the benefits of design. In this paper, we want to identify the underlying challenges that explain this gap. We are especially interested in the role and challenges of design in interdisciplinary product development. Therefore, we perform a literature review that clarifies terminology, analyses research approaches and identifies challenges. We determine seven key challenges for design in interdisciplinary product development. Furthermore, we observe a limited scope of research approaches in the reviewed literature. Based on these findings, we propose three further research directions to strengthen the role of design in interdisciplinary product development in the future.

Designing Business Models for a Circular Economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The megatrend sustainability will significantly change the future value creation of manufacturing companies. Their current linear value creation models need to change to conform to the requirements of sustainability. To face the challenges the circular economy has emerged as a promising economic model. With the shift from a linear to a circular economy, companies have to adjust their current business models. However, they still lack knowledge and adequate methods to develop circular business models. Hence, the aim of the paper is a circular business model canvas (CBMC) for designing circular businesses. A systematic literature review was conducted to identify significant criteria for circular business models. The criteria were analyzed utilizing a qualitative content analysis to derive the business model elements required for the circular economy. Existing elements from the Business Model Canvas were enriched and five new elements, e.g., reverse logistics, were found. Then, the business model elements were logically arranged resulting in the CBMC. It guides companies to systematically develop business models for the circular economy. The CBMC was evaluated by applying it within a mediumsized company in the electronics sector.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.

Higher order interactions lead to "reluctant" synchrony breaking - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (arXiv:2311.17186)
To model dynamical systems on networks with higher order (non-pairwise) interactions, we recently introduced a new class of ODEs on hypernetworks. Here we consider one-parameter synchrony breaking bifurcations in such ODEs. We call a synchrony breaking steady state branch "reluctant" if it is tangent to a synchrony space, but does not lie inside it. We prove that reluctant synchrony breaking is ubiquitous in hypernetwork systems, by constructing a large class of examples that support it. We also give an explicit formula for the order of tangency to the synchrony space of a reluctant steady state branch.

Privacy in the Age of Neurotechnology: Investigating Public Attitudes towards Brain Data Collection and Use - Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

Runtime Verification of Crypto APIs: An Empirical Study - Torres, Adriano; Costa, Pedro; Amaral, Luis; Pastro, Jonata; Bonifácio, Rodrigo; d'Amorim, Marcelo; Legunsen, Owolabi; Bodden, Eric; Dias Canedo, Edna (IEEE Transactions on Software Engineering)
Keywords: Software

Can the configuration of static analyses make resolving security vulnerabilities more effective? - A user study - Piskachev, Goran; Becker, Matthias; Bodden, Eric (Empirical Software Engineering)
Abstract The use of static analysis security testing (SAST) tools has been increasing in recent years. However, previous studies have shown that, when shipped to end users such as development or security teams, the findings of these tools are often unsatisfying. Users report high numbers of false positives or long analysis times, making the tools unusable in the daily workflow. To address this, SAST tool creators provide a wide range of configuration options, such as customization of rules through domain-specific languages or specification of the application-specific analysis scope. In this paper, we study the configuration space of selected existing SAST tools when used within the integrated development environment (IDE). We focus on the configuration options that impact three dimensions, for which a trade-off is unavoidable, i.e., precision, recall, and analysis runtime. We perform a between-subjects user study with 40 users from multiple development and security teams - to our knowledge, the largest population for this kind of user study in the software engineering community. The results show that users who configure SAST tools are more effective in resolving security vulnerabilities detected by the tools than those using the default configuration. Based on post-study interviews, we identify common strategies that users have while configuring the SAST tools to provide further insights for tool creators. Finally, an evaluation of the configuration options of two commercial SAST tools, Fortify and CheckMarx , reveals that a quarter of the users do not understand the configuration options provided. The configuration options that are found most useful relate to the analysis scope.
Keywords: Software

Securing Your Crypto-API Usage Through Tool Support - A Usability Study - Krüger, Stefan; Reif, Michael; Wickert, Anna-Katharina; Nadi, Sarah; Ali, Karim; Bodden, Eric; Acar, Yasemin; Mezini, Mira; Fahl, Sascha (2023 IEEE Secure Development Conference (SecDev))

Entwicklung und Analyse von Formeln zur Abschätzung der Renderingzeit eines Frames - Nickel, Alexander

Reconstruction of 3D Surfels from Neural Radiance Fields - Telaprolu, Vipasyan